The Phenomenon of Social Loafing among Guidance and Counseling Students Viewed from the Perspective of Gestalt Counseling Theory - Riskiyana Prihatiningsih; Erna Puji Lestari; Ella Faridati Zen (Universitas Mercu Buana Yogyakarta, 2025)
Social loafing is the tendency of individuals to reduce their contribution when they are in a group. This phenomenon reflects maladaptive personal characteristics, which ideally should not be exhibited by Guidance and Counseling students at a university in Malang City. This study aims to explore views, actions, and causal factors of social loafing from the perspective of personality development based on Gestalt counseling theory. The research method used a qualitative phenomenological approach and Interpretative Phenomenological Analysis. The results of the study show that social loafing is a reflection of maladaptive personality in Gestalt counseling theory. This is indicated by views related to an incomplete awareness of roles when working in a group. In addition, there is also evidence of behavior that is less motivated and responsible as part of a group. The causes of the social loafing phenomenon identified are a rigid self-image and failure to maintain values due to environmental influences. This research contributes to guidance and counseling, particularly in higher education, with considerations for implementing both preventive and corrective services related to social loafing. Furthermore, it can also serve as a reference for the education sector to provide a group work environment that reduces social loafing among members.